Effects of ultrasound-induced structural modifications on the emulsifying properties of Tenebrio molitor proteins - Yun Jae Jang; Hyeong Do Kim; Yu Ji Ye; Ming Kong; Woo Su Lim; Min Hyeock Lee (Ultrasonics Sonochemistry)
Ultrasonication has emerged as a promising technique for modifying physicochemical properties of proteins, enhancing their functionality in food applications. This study evaluated the effects of ultrasonic treatment on the structural and functional properties of mealworm-derived proteins (MPs) and their potential as emulsifiers. Dynamic light scattering revealed a significant reduction in MP particle size from 3464.3 nm (untreated) to 115.5 nm (30 min sonication), along with increased zeta potential, indicating improved colloidal stability. Sonication enhanced oil-holding capacity and solubility, suggesting improved interfacial adsorption and emulsification. Circular dichroism and FT-IR spectroscopy confirmed structural modifications, including increased α-helix content and enhanced hydrogen bonding interactions. Free sulfhydryl content and surface hydrophobicity analyses indicated ultrasound-induced unfolding, exposing functional groups that contribute to emulsifying properties. Sonicated MPs demonstrated superior emulsion stability under varying temperature, pH, and ionic conditions. Furthermore, digestibility analysis showed improved gastric digestion (72.7 % to 82.8 %) and enhanced lipid digestion in the small intestine (36.2 % to 47.9 %), suggesting greater bioavailability. These physicochemical modifications highlight the feasibility of using sonicated MP as natural emulsifiers with enhanced functionality. This study underscores their potential in food formulations, particularly for nutritionally fortified emulsions, contributing to sustainable and functional food ingredient development.